Hospital management and outcomes of stroke in Indigenous Australians: evidence from the 2009 Acute Care National Stroke Audit. Issue 3 (2nd February 2012) - Kilkenny, Monique F.; Harris, Dawn M.; Ritchie, Elizabeth A.; Price, Chris; Cadilhac, Dominique A.; ,
<x xml:space="preserve">Abstract</x> Background Indigenous Australians have greater stroke mortality rates than non‐Indigenous people (97% Indigenous Australians are aged <65 years). Quality of care in hospital is an important factor for avoiding death and disability. No national review of acute stroke care for Indigenous Australians is available. Aims We aimed to compare adherence with clinical processes and outcomes among Indigenous and non‐Indigenous patients with acute stroke admitted to hospital. Methods Hospitals participating in the National Stroke Audit of acute services in 2009 that provided data for at least one Indigenous patient were included (n = 33, 37%). Differences in death/dependency (modified Rankin Score 3–6) at discharge were determined using two‐level multivariate analysis adjusting for hospital site and patient variables. A matched subgroup analysis in those aged 18 to 64 years was also undertaken. Results Among 1162 eligible patients (60% male; 18–64 years n = 305), 7% were Indigenous (18–64 years: 18%). Indigenous patients had a greater prevalence of stroke risk factors, e.g. diabetes, more had intracerebral hemorrhages (25% vs. 16% non‐Indigenous, P = 0·05), and were less likely be treated in a stroke unit and receive timely allied health assessments than non‐Indigenous patients. Indigenous patients aged 18–64 years had a threefold odds of dying or being dependent at discharge (Adjusted odds ratio = 3·09, 95% confidence interval = 1·07–8·95). Conclusions Australian Indigenous patients with stroke received a reduced quality of care in hospitals and experienced worse outcomes than non‐Indigenous patients. Indigenous patients require the provision of evidence‐based care to increase their opportunities for optimal health outcomes following stroke. Further research to explain the differences is needed.